Development and Validation of a GC-MS Method for the Detection and Quantification of Clotiapine in Blood and Urine Specimens and Application to a Postmortem Case. (7th July 2015) - Mannocchi, Giulio; Pantano, Flaminia; Tittarelli, Roberta; Catanese, Miriam; Umani Ronchi, Federica; Busardò, Francesco Paolo
Abstract : Introduction . Clotiapine is an atypical antipsychotic of the dibenzothiazepine class introduced in a few European countries since 1970, efficient in treatment-resistant schizophrenic patients. There is little published data on the therapeutic and toxic concentrations of this drug. Aims . The aim of the present study is the development and validation of a method that allows the detection and quantification of clotiapine in blood and urine specimens by gas chromatography-mass spectrometry (GC-MS). Methods . Validation was performed working on spiked postmortem blood and urine samples. Samples were extracted with liquid-liquid extraction (LLE) technique at pH 8.5 with n-hexane/dichloromethane (85/15 v/v) and analysis was followed by GC-MS. Methadone-d9 was used as internal standard. Results . The limit of detection (LOD) was 1.2 and 1.3 ng/mL for urine and blood, respectively, while the lower limit of quantification (LLOQ) was 3.9 and 4.3 ng/mL, respectively. Linearity, precision, selectivity, accuracy, and recovery were also determined. The method was applied to a postmortem case. The blood and urine clotiapine concentrations were 1.32 and 0.49 μ g/mL, respectively. Conclusions . A reliable GC-MS method for the detection and quantification of clotiapine in blood and urine samples has been developed and fully validated and then applied to a postmortem case.